The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/2177-6709.26.2.e2119378.oar
|View full text |Cite
|
Sign up to set email alerts
|

Separation of aligning and leveling stages to control mandibular incisor inclination: A randomized clinical trial

Abstract: Objective: To determine whether separating the alignment and leveling phases can reduce proclination of the mandibular incisors. Methods: Eligibility criteria included Class I subjects with an irregularity index of 3-5 mm, 3-4 mm curve-of-Spee (COS), and non-extraction treatment. Thirty adults were randomly allocated into two groups: (1) Control group was leveled and aligned simultaneously with flat archwires progressively to 0.016x0.022-in stainless-steel; (2) Experimental group was aligned first with 0.014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Although less lower incisor proclination in group 3 might be anticipated due to less bracket slot-AW play, this was not the case in this investigation. Lower incisor proclination might have occurred as the intrusive force application by reverse COS is anterior to the center of resistance [28]. This finding is in line with others who suggested that excessive incisor tipping may result from high intrusive forces at the incisor brackets creating tipping moments on each incisor and that could happen with increase AW dimensions [29].…”
Section: Discussionsupporting
confidence: 79%
“…Although less lower incisor proclination in group 3 might be anticipated due to less bracket slot-AW play, this was not the case in this investigation. Lower incisor proclination might have occurred as the intrusive force application by reverse COS is anterior to the center of resistance [28]. This finding is in line with others who suggested that excessive incisor tipping may result from high intrusive forces at the incisor brackets creating tipping moments on each incisor and that could happen with increase AW dimensions [29].…”
Section: Discussionsupporting
confidence: 79%
“…To comprehend the impact of the depth of the COS on dental alignment, one must consider several elements, including the relationships between the anterior and posterior teeth [18], the angle at which the incisors are positioned [19], the patterns of vertical tooth eruption [20], and the functional alignment of the teeth during mastication [21]. These aspects illustrate how a pronounced COS can exacerbate malocclusions, affect tooth orientation, and influence vertical and horizontal teeth relationships [22], ultimately guiding the strategic approaches in orthodontic and restorative dental treatments [23].…”
Section: Of 16mentioning
confidence: 99%
“…Fase levelling dan aligning adalah keadaan mahkota gigi digerakkan dalam waktu bersamaan dan arah gerak yang berbeda. 5 Kawat NiTi memiliki sifat elastisitas dan shape memory effect yang baik. 6 Perawatan ortodonti bergantung pada kondisi kawat ortodonti.…”
Section: Pendahuluanunclassified